IMPLEMENTASI PROGRAM BADAN USAHA MILIK KAMPUNG (BUM KAMPUNG) DI KAMPUNG TUMANG KECAMATAN SIAK KABUPATEN SIAK - Anuar Sadat; Ledi Prahmana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2019)
Village-Owned Enterprises (BUM Kampung) are a pillar of economic activities in the village that function as social institutions and commercial institutions. As an indicator to regulate the economy in the village. The formulation of the problem in this study are: 1. How to Implement the Village-Owned Enterprises (BUMKampung) Program in Tumang Village, Siak District, Siak Regency. 2. What is the Function of the Kampung (BUMKampung) Village of Tumang, Siak District of Siak Regency and How is the Analysis of BUMKampung Program Policy Implementation. The objectives of this study were: 1) To find out the Program of Village Owned Enterprises (BUMKampung) in Tumang Village, Siak Subdistrict, Siak Regency, 2) Know the Implication of the Policy of Village-Owned Enterprises (BUM Kampung) in Tumang Village, Siak District, Siak Regency and Find Conclusions on Implementation Analysis Program Policies for Village Owned Enterprises (BUM Kampung) in Tumang Village, Siak District, Siak Regency. The method used in this research is descriptive qualitative data that is qualitative in a holistic analysis, the classification of data used in this study is Primary data, data obtained by interviewing informants, the public, and management of BUM Kampung in Kampung Tumang. Data was collected using techniques: observation, interviews, literature study, documentation studies, research informants. The results of this study concluded that the implementation of the BUM Kampung program had gone well.